ICT САБАҒЫНДА CLIL ƏДІСІН ҚОЛДАНЫП ТІЛДІК ҚҰЗІРЕТТІЛІКТІ ҚАЛЫПТАСТЫРУ - Айтбенова, А.А. (My University, 2019)
Аннотация Ұсынылған мақалада CLIL пəн мен тілді кіріктіріп оқыту əдісі, оның артықшылығы туралы жəне оны жоо-да Information and Communication Technologies (ICT) сабағында қолдану туралы айтылған. Сонымен қатар, ICT сабақтарында қолдануға болатын кейбір белсенді əдістер мен тəсілдер қарастырылған. Abstract The proposed article discusses the method of integrated learning of the subject and language - CLIL, its advantages and its use in the classes of Information and Communication Technologies (ICT) at the university. In addition, there are some active methods and techniques that can be used in ICT lessons.
Formation of language competence using the CLIL method in ict
Keywords: CLIL (Content Language Integrated Learning) əдісі; nformation and Com- munication Technologies (ICT); таңбалау; бос орындарды толтыру; салыстыру; тестілеу; кроссворд; method CLIL (Content Language Integrated Learning); Information and Communication Technologies (ICT); labelling; fill gap; matching; tests; crossword